Kewenangan Rumah Sakit Dalam Pengambilan Keputusan Merujuk Pasien Ke Rumah Sakit Yang Tidak Disetujui Keluarga Pasien - Rahmadi Mulyo Widianto; Sekaring Ayumeida Kusnadi (Darma Cendika Catholic University, 2026)
This study examines the legal dilemma faced by private hospitals not yet partnered with Indonesia’s national health insurance (BPJS Kesehatan) when referring critically ill patients whose families reject the recommended referral hospital after their preferred facility reaches full capacity. It analyzes the legal authority and legal protection available to hospitals in making referral decisions without family consent, and repositions that authority within the current legal framework following Law No. 17 of 2023 on Health, which revoked Law No. 44 of 2009 on Hospitals. Using normative legal research with a statute approach and a conceptual approach grounded in authority theory (attribution, delegation, mandate), the study finds that hospitals hold attributive authority to refer patients once they perform patient stabilization, inter-facility communication, and referral documentation as required by Article 14 paragraph (4) of Minister of Health Regulation No. 4 of 2018, a provision that remains valid as an implementing regulation despite the enactment of Law No. 17 of 2023. Hospitals that comply with this procedure are legally protected under Article 193 of Law No. 17 of 2023, while families who reject a medically and administratively appropriate referral must bear the resulting costs or independently file a reimbursement claim with BPJS Kesehatan.